Relatório de estágio técnico profissional supervisionado em medicina veterinária: controle de qualidade - Gandini, Micheli (2023)
With the aim of putting into practice the lessons learned during the Veterinary Medicine degree, the Professional Technical Internship (ETP) was carried out in the area of ​​Milk and Dairy Products Quality Control and Control, under the academic guidance of Prof. Dr. Luciana Ruschel dos Santos. The ETP was carried out at the company Lacticínios Bio, located in the city of Boa Vista do Sul – RS, 230km from Passo Fundo, from 07/17/2023 to 10/15/2023. The company receives an average of 68 thousand liters of milk per day, which is used to produce colonial cheese, mozzarella cheese, snack cheese, fresh cheese and fresh ricotta, dairy drinks, yogurt, cream, cottage cheese and desserts. Monitoring of the reception of the refrigerated raw product was carried out, with fraud research carried out (acidity neutralizer, formaldehyde, hydrogen peroxide, sucrose, starch, ethyl alcohol and chlorides) in all tanks, as well as monitoring of physical-chemical analyzes and microbiological aspects of ready-made products. It is concluded that the ETP was of paramount importance for personal and professional development, since it was an opportunity to experience the routine that is found in everyday life in the job market, in addition, the importance of quality control was observed ( QC) within a company.